EU health solidarity in times of crisis: explaining public preferences towards EU risk pooling for medicines. Issue 8 (3rd August 2022) - Baute, Sharon; de Ruijter, Anniek
ABSTRACT: The COVID-19 outbreak in Europe has brought attention to EU health policy as a focal point for solidarity, particularly as it concerns access to medicines. Against the backdrop of policy proposals for EU joint procurement of medicines, this article expands our understanding of public opinion towards this particular aspect of European integration. Drawing on data from a conjoint experiment in five EU countries, the study investigates the extent to which citizens' preferences concerning alternative policy designs for EU joint procurement of medicines are either structured along a pro-EU versus anti-EU or ideological divide, or are crisis driven by the perceived COVID-19 threat. The analysis reveals that individual preferences over the design of EU risk pooling for medicines are most strongly explained by Euroscepticism, while egalitarian ideology plays only a modest role. How citizens' perceived threat of COVID-19 affects their preferences for this form of EU risk pooling is dependent on the national context.